Reduced Prepulse Inhibition as a Biomarker of Schizophrenia - Mena, Auxiliadora; Ruiz-Salas, Juan C.; Puentes, Andrea; Dorado, Inmaculada; Ruiz-Veguilla, Miguel; De la Casa, Luis G. (Frontiers in Behavioral Neuroscience, 2016)
The startle response is composed by a set of reflex behaviors intended to prepare the organism to face a potentially relevant stimulus. This response can be modulated by several factors as, for example, repeated presentations of the stimulus (startle habituation), or by previous presentation of a weak stimulus (Prepulse Inhibition). Both phenomena appear disrupted in schizophrenia that is thought to reflect an alteration in dopaminergic and glutamatergic neurotransmission. In this paper we analyze whether the reported deficits are indicating a transient effect restricted to the acute phase of the disease, or if it reflects a more general biomarker or endophenotype of the disorder. To this end, we measured startle responses in the same set of thirteen schizophrenia patients with a cross-sectional design at two periods: Five days after hospital admission and three months after discharge. The results showed that both startle habituation and Prepulse Inhibition were impaired in the schizophrenia patients at the acute stage as compared to a control group composed by 13 healthy participants, and that Prepulse Inhibition but not startle habituation remained disrupted when registered three months after the discharge. These data point to the consideration of Prepulse Inhibition, but not startle habituation, as a schizophrenia biomarker.